Arte consumo y sociedad - Galarza Robles, Diana Elizeth (2018)
The present work is directed toward an artistic proposal on the homo-comsumens and identity. In which we can show how society, is exposed to different changes as loss of identity and culture, these are caused by consumerism, and even by the technological advances that today is almost flaunted the society, through these media society adopt cultures not belonging to their environment and leave aside their customs. The advertisements that produces television and visual pollution make society is driven to further increase its consumption for the reason that they constantly pending the new brands that will go on sale in order to acquire them. This society has become so independence, do not fail to take advantage of the opportunities to purchase and it is here where it takes possession of the credit card in order to facilitate the consumer to do your shopping without any inconvenience. To perform this work, it was decided to search for focused to perform work which is based on consumerism and art installation and thus to be able to contribute to the development of the same, it is worth mentioning that not only in the present, there are artists that address this topic, found information about a deceased renowned artist focused on this issue of a social nature, in this way it is possible to observe that the habit of eating has been present ever since. Through the implementation of research can be evidenced as at present the human being persuaded by the hierarchical powers to induce them to consume. Art installation was chosen to be a medium in which you can make a visual tour where the viewer can interact and manipulate the work, and at the same time we served as support to corroborate the knowledge of the public toward the consumer brands and, through criticism, we were able to show how a certain number of people are identified each of the brands exposed, thus showing their interest in them. However, it should be noted that, in spite of everything, if there are people who consume responsibly the brands that the market offers. The work carried out with twelve critical areas which symbolize the months of the year, as a criticism of the society that differs from their purchases to the months mentioned above, as well have the possibility of buying, with more comfort and get involved to the world of consumption the marks used in this critique, represented as society gets carried away by the vanities, leaving to one side their real estate. In this way the work called "System" reaches the viewer causing impact and at the same time recognize that men and women are attracted by different brands that lead to consume constantly, in this way, show how the work fulfilled the purpose for which it was created. The result obtained in the development of this research was satisfactory, to comply with what is proposed in the realization of the work viewers had the opportunity to interact and get to feel how the marks are kept wrapped in a consumerist world.